Outcomes in Rhinoplasty - Saleh, Hesham A.; Beegun, Issa; Apaydin, Fazil (Facial Plastic Surgery, 2019)
In recent years, there is an increasing trend to use health-related quality of life questionnaires after surgical procedures. The idea is to prove the success of an operation by objectively measurable parameters. Rhinoplasty is by far the most frequently performed surgery of facial plastic surgery. One of the most difficult parts of rhinoplasty is to measure the outcomes after surgery. Rhinoplasty is a unique operation because the surgeon affects three aspects: shape, function, and psychology of the patient. In an ideal world, the surgeon should have objective means of screening that cover these three aspects before and after surgery to measure outcomes. The goal of this article is to review these tools and compare them.
Keywords: facial plastic surgery; rhinoplasty; outcome measure